Options for flexibilisation within the scope of the BBiG and its implementation - Hackel, Monika [Verfasser] (My University, 2022)
"The wish for a more flexible structuring of vocational education and training is particularly expressed within the context of dynamic innovation and transformation processes in Germany. One thing which is frequently overlooked is the fact that the German vocational training act (BBiG) already offers options for flexibilisation in relation to the structures and contents of training occupations, with regard to implementation in terms of place and time, and in respect of specific groups of persons. These options are described in the present article. Nevertheless, it is revealed that some of them are used only hesitantly. The questions which therefore arise are whether there is sufficient awareness of these options, whether further options are required and which prerequisites these would need to fulfil." (author's abstract)
Keywords: S 1 Stufen der Berufsbildung; S 2.1.1 Berufsbildungsgesetz (BBiG); 370; Berufsbildung; Berufsbildungsgesetz; Flexibilisierung